2016
DOI: 10.2337/dc16-1889
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiovascular Risk Factors and Myocardial Fibrosis With Early Cardiac Dysfunction in Type 1 Diabetes: The Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications Study

Abstract: OBJECTIVEWe investigated the association of cardiovascular risk factors and myocardial fibrosis with early cardiac dysfunction in type 1 diabetes.RESEARCH DESIGN AND METHODSParticipants with type 1 diabetes aged 13–39 years without a known history of cardiovascular disease (CVD) (n = 1,441) were recruited into the Diabetes Control and Complications Trial (1983–1993) and subsequently followed in the Epidemiology of Diabetes Interventions and Complications study (1994 to present). Seven hundred fourteen particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Extensive clinical evidence has documented the presence of myocardial fibrosis in patients with diabetes [9, 38]. Many histopathological studies have also confirmed that cardiac fibrosis caused by diabetes occurs independently of hypertension or coronary atherosclerosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive clinical evidence has documented the presence of myocardial fibrosis in patients with diabetes [9, 38]. Many histopathological studies have also confirmed that cardiac fibrosis caused by diabetes occurs independently of hypertension or coronary atherosclerosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…HbA 1c is also an important predictive marker of long term complications of diabetes ( 4 , 5 ). HbA 1c assays can be performed using different analytical principles including separative methods such as high performance liquid chromatography (HPLC) and capillary electrophoresis, but also immunological and enzymatic methods.…”
Section: Introductionmentioning
confidence: 99%
“…We acknowledge that many factors are at play in determining the PCr/ATP equilibrium, including rates of mitochondrial oxidative phosphorylation, microvascular dysfunction and the presence of cardiac fibrosis. The latter refers to the fact that people with T1D are known to have increased myocardial fibrosis (Armstrong et al., ), an observation that would imply that their cardiomyocytes have to work at a higher workload per cell to compensate for the smaller LV volume fraction. This would not only lead to an inability in maintaining the PCr/ATP ratio, but also a lower maximal cardiac output and V̇O2max.…”
Section: Type 1 Diabetes: Beyond Skeletal Musclementioning
confidence: 99%